2013
DOI: 10.1007/s10067-013-2385-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF therapy in patients with HBV infection—analysis of 87 patients with inflammatory arthritis

Abstract: This study aims to investigate the incidence of hepatitis B virus (HBV) reactivation in inflammatory arthritis (IA) patients with HBV infection using anti-tumor necrosis factor (TNF) agents and evaluate the efficacy of antiviral therapy in reducing the risk of viral reactivation in chronic HBV infection. IA patients using anti-TNF agents from six centers were enrolled. Their HBV infection conditions and ALT and HBV-DNA levels were monitored periodically. Among the six chronic hepatitis B patients, HBV reactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 10 publications
1
33
0
8
Order By: Relevance
“…24,25 A recent study analyzing patients with inflammatory arthritis also revealed an increased risk of HBV reactivation associated with anti-TNF therapy in patients with chronic HBV infection. 41 However, due to limited wellcontrolled studies, the association between TNF-a blockage and HBV reactivation remains uncertain. In this study, we further addressed the dynamic change of HBV viral load in blockage of TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 A recent study analyzing patients with inflammatory arthritis also revealed an increased risk of HBV reactivation associated with anti-TNF therapy in patients with chronic HBV infection. 41 However, due to limited wellcontrolled studies, the association between TNF-a blockage and HBV reactivation remains uncertain. In this study, we further addressed the dynamic change of HBV viral load in blockage of TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…The available data reported in literature do not provide clear indications on the anti-TNF-α agents of choice with regard to the safety in patients exposed to HBV. In older reports, INF was associated to higher risk of HBV reactivation, mainly due to its pharmacological characteristics [84], but several case reports [59,64,69,[85][86][87][88][89][90][91] and studies [53,57] highlighted reactivations during treatment with ETA; similar results can be found with ADA [49,63,66].…”
Section: Resultsmentioning
confidence: 79%
“…The second prospective study reported by Ye H et al [57] was conducted from January 2008 to January 2011 in six centers in China. 87 patients enrolled with HBV and inflammatory arthritis (RA, SpA, and PA) were followed up every 1-3 months until January 2012.…”
Section: Citationmentioning
confidence: 99%
“…However, Lee et al [49] reported that HBV reactivation occurred in 1.7% among 468 rheumatic patients with resolved HBV infection during anti-TNF therapy. Ye et al [58] reported that HBV reactivation was not found in the 50 patients with resolved HBV infection. Recent prospective study also demonstrated that none of 146 rheumatic patients with resolved HBV infection who received anti-TNF developed HBV reactivation during 56 months follow-up periods.…”
Section: Incidence and Clinical Outcomes Of Hbv Reactivation In Patiementioning
confidence: 99%
“…All 5 patients recovered after treatment of lamivudine. A recent prospective study [58] investigated the incidence of HBV reactivation in inflammatory arthritis patients with HBV infection using anti-TNF therapy and evaluated the efficacy of antiviral therapy. Among the 6 chronic hepatitis B patients (defined by HBV DNA > 2×10 4 IU/mL, elevated ALT), HBV reactivation occurred in two patients (33.3%) without antiviral prophylaxis and no HBV reactivation was observed in the other 4 patients with antiviral prophylaxis.…”
Section: Incidence and Clinical Outcomes Of Hbv Reactivation In Patiementioning
confidence: 99%